Acute Renal Failure with Metabolic Alkalosis Due to Gastric Scirrhous Carcinoma. Issue 2 (24th December 2014) - Shikino, Kiyoshi; Ikusaka, Masatomi; Hayashi, Haruyuki; Ohtake, Yoshio; Irie, Yasubumi
Abstract : A 51‐year‐old man was emergently admitted for acute renal failure. Blood tests showed a high serum creatinine level and metabolic alkalosis. He had a history of recurrent vomiting starting one month prior to admission to our hospital, and had circumferential thickening of the cardia on upper gastrointestinal endoscopy and CT. He underwent total gastrectomy and was given a diagnosis of scirrhous gastric carcinoma at the pylorus. After total gastrectomy, acute renal failure and metabolic alkalosis showed amelioration. We report this very rare case with metabolic alkalosis and acute renal failure resulting from pyloric stenosis caused by scirrhous gastric carcinoma.